2021
DOI: 10.1063/5.0037452
|View full text |Cite
|
Sign up to set email alerts
|

Disease transmission through expiratory aerosols on an urban bus

Abstract: Airborne respiratory diseases such as COVID-19 pose significant challenges to public transportation. Several recent outbreaks of SARS-CoV-2 indicate the high risk of transmission among passengers on public buses if special precautions are not taken. This study presents a combined experimental and numerical analysis to identify transmission mechanisms on an urban bus and assess strategies to reduce risk. The effects of the ventilation and air-conditioning systems, opening windows and doors, and wearing masks ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
122
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(125 citation statements)
references
References 43 publications
(28 reference statements)
2
122
0
1
Order By: Relevance
“…Current federal mandates require masking during bus transportation; however, ventilation with open windows is recommended but not mandated. While there is little data on how ventilation on buses affects transmission of COVID‐19, the opening of doors or windows on a bus can reduce the number of aerosol droplets by half 17 . In the present study, the consistent spaced window openings on each school bus, regardless of weather, may have significantly contributed to the lack of transmission of SARS‐CoV‐2.…”
Section: Discussionmentioning
confidence: 57%
“…Current federal mandates require masking during bus transportation; however, ventilation with open windows is recommended but not mandated. While there is little data on how ventilation on buses affects transmission of COVID‐19, the opening of doors or windows on a bus can reduce the number of aerosol droplets by half 17 . In the present study, the consistent spaced window openings on each school bus, regardless of weather, may have significantly contributed to the lack of transmission of SARS‐CoV‐2.…”
Section: Discussionmentioning
confidence: 57%
“…In this paper, we consider the smallest aerosols only, those with diameter less than 10 µ m. Under this assumption, aerosols are represented with the continuum field C = C ( x , t ), which is transported passively with the unsteady RANS (URANS) velocity field [ Zhang et al (2021) ]. Details on both the well-mixed model and CFD simulations are summarized herein.…”
Section: Modeling Of Aerosol Transportmentioning
confidence: 99%
“…A gradient limiter is used to ensure that the interpolation from cell centers to face centers produces a bounded and stable solution. Additional details, including a mesh refinement study, can be found in Zhang et al (2021) . The custom solver is available on GitHub ( https://github.com/zhihangz/covid-transmission ).…”
Section: Modeling Of Aerosol Transportmentioning
confidence: 99%
“…Since the experiments conducted in this study suggest that majority of the aerosol particles have a size of less than 1 µm, the distribution of the aerosols at the scale of a classroom can be modeled using the Eulerian approach, by solving the transport equation accounting for convection-diffusion of the aerosol (Z. Zhang et al, 2021). The effective diffusive constant for the aerosol is the sum of the molecular and turbulent contributions, = ⁄ + ⁄ , where Pr = 0.7 and Prt = 0.85, are the laminar and turbulent Prandtl numbers, respectively, with values that are generally used for the modeling of aerosol transport in ventilation cases (Burgmann & Janoske, 2021).…”
Section: Computational Fluid Dynamics Calculationsmentioning
confidence: 99%